Pregunta
upstudy study bank question image url

Write the given expression in the form \( f(x)=a(x-h)^{2}+k \). Identify the vertex. \( f(x)=3 x^{2}-24 x-5 \)

Ask by Summers Schofield. in the United States
Dec 11,2024

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The expression in vertex form is \( f(x) = 3(x - 4)^2 - 53 \) and the vertex is \( (4, -53) \).

Solución

To rewrite the expression \( f(x) = 3x^2 - 24x - 5 \) in the form \( f(x) = a(x-h)^2 + k \), we will complete the square. 1. **Factor out the coefficient of \( x^2 \)** from the first two terms: \[ f(x) = 3(x^2 - 8x) - 5 \] 2. **Complete the square** for the expression inside the parentheses. To do this, take the coefficient of \( x \) (which is \(-8\)), divide it by 2 (getting \(-4\)), and then square it (getting \(16\)): \[ f(x) = 3(x^2 - 8x + 16 - 16) - 5 \] This simplifies to: \[ f(x) = 3((x - 4)^2 - 16) - 5 \] 3. **Distribute the 3**: \[ f(x) = 3(x - 4)^2 - 48 - 5 \] \[ f(x) = 3(x - 4)^2 - 53 \] Now, we have the expression in the form \( f(x) = a(x-h)^2 + k \): - \( a = 3 \) - \( h = 4 \) - \( k = -53 \) Thus, the vertex of the parabola is at the point \( (h, k) = (4, -53) \). In summary, the expression in vertex form is: \[ f(x) = 3(x - 4)^2 - 53 \] And the vertex is: \[ (4, -53) \]

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To rewrite the expression \( f(x) = 3x^2 - 24x - 5 \) in vertex form \( f(x) = a(x-h)^2 + k \), we need to complete the square. First, factor out the coefficient of \( x^2 \) from the first two terms: \[ f(x) = 3(x^2 - 8x) - 5 \] Next, complete the square inside the parentheses. Take half of the coefficient of \( x \) (which is \(-8\)), square it, and add and subtract that value inside the parentheses. Half of \(-8\) is \(-4\), and squaring it gives \(16\): \[ f(x) = 3(x^2 - 8x + 16 - 16) - 5 \] Now, we can simplify it: \[ f(x) = 3((x - 4)^2 - 16) - 5 \] \[ = 3(x - 4)^2 - 48 - 5 \] \[ = 3(x - 4)^2 - 53 \] Thus, the expression in vertex form is: \[ f(x) = 3(x - 4)^2 - 53 \] The vertex is at the point \( (h, k) = (4, -53) \).

preguntas relacionadas

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad